Characteristics of interfacial signatures on a wind-driven gravity-capillary wave - Tsai, Wu-Ting; Chen, Shi-ming; Lu, Guan-hung; Garbe, Christoph S. (Journal of geophysical research. Oceans, 2013)
Direct numerical simulation of a wind-driven gravity-capillary wave and the underlying turbulent flow is conducted to identify the characteristic signatures of various surface parameters, including temperature, gas flux, velocities, and roughness, and to reveal the impacts of the nonbreaking surface waves on these surface flow and tracer parameters. Three characteristic surface signatures and the corresponding flow processes are identified: the carrier gravity wave, the parasitic capillary wavelets, and the elongated streaks. The elongated streaks are induced by both the coherent streamwise vortices formed within the turbulent shear layer and the Langmuir circulations arising from nonlinear interaction between the carrier gravity wave and the drift current. All three surface signatures can be observed in the distributions of various quantities, although some are more apparent than the others. Image-processing techniques, employing empirical mode decomposition and phase averaging, are developed to decompose the distinct signatures thus to quantify the contributions by the responsible flow processes. It is found that elongated streaks prevail the distribution of surface temperature and gas flux, indicating that Langmuir cells and the coherent eddies contribute to the major interfacial heat and gas transport. These eddies also induced strong cross-stream velocity divergence at the water surface, which exhibits resemblant elongated distribution as that of gas flux (correlation coefficient ≈ 0.6). High correlation between the surface distributions of temperature and gas flux is observed (correlation coefficient ≈ 0.8 to 0.9), suggesting that the spatial and temporal distribution of surface temperature is a good proxy tracer of interfacial gas transfer.
Gesehen am 14.02.2022